Service quality and its effect on inpatient satisfaction at Purwodadi islamic hospital - Nanang Handoko; Siti Dyah Handayani (Universitas Aisyah Pringsewu, 2023)
Service quality can be a driving force that is created and perceived by patients in order to establish a relationship that can provide long-term mutual benefits with the hospital. Service quality will affect patient satisfaction, thus encouraging patients to continue using hospital services when needed. The purpose of this study was to determine the effect of service quality on patient satisfaction. This research is a case study with a cross-sectional design. The population is inpatients at RSI Purwodadi. A sample of 100 patients was taken by purposive sampling. Data collection used a questionnaire. Data analysis technique used multiple linear regression. The results showed that service quality significantly affected patient satisfaction with an F of 14.641 and a p of 0.000 (p less than 0.05). The tangible dimension of service quality has no effect on patient satisfaction (t = 0.809, p = 0.421). As for service quality, the dimensions of reliability (t = 2.028, p = 0.045), responsiveness (t = 3.135, p = 0.002), assurance (t = 2.613, p = 0.010), and empathy (t = 2.480, p = 0.015) have a positive effect and significant to patient satisfaction. The study concludes that service quality has a significant effect on patient satisfaction. The tangible dimension of service quality does not affect patient satisfaction. Service quality dimensions of reliability, responsiveness, assurance, and empathy positively and significantly affect patient satisfaction. Abstrak: Kualitas pelayanan dapat menjadi pendorong yang diciptakan dan dipersepsikan pasien dalam rangka menjalin sebuah hubungan relasi yang dapat saling memberikan keuntungan jangka panjang dengan rumah sakit. Kualitas pelayanan akan berpengaruh terhadap kepuasan pasien, sehingga mendorong pasien terus menggunakan pelayanan rumah sakit ketika membutuhkan. Tujuan penelitian ini adalah untuk mengetahui pengaruh kualitas pelayanan terhadap kepuasan pasien. Penelitian merupakan studi kasus dengan rancangan cross sectional. Populasi adalah pasien rawat inap RSI Purwodadi. Sampel sejumlah 100 pasien diambil dengan purposive sampling. Pengumpulan data digunakakan kuesioner. Teknik analisis data digunakan regresi linier berganda. Hasil penelitian menunjukkan bahwa kualitas pelayanan berpengaruh signifikan terhadap kepuasan pasien, dengan F sebesar 14,641 dan p sebesar 0,000 (p kurang dari 0,05). Kualitas pelayanan dimensi tangible tidak berpengaruh terhadap kepuasan pasien (t= 0,809, p= 0,421). Adapun kualitas pelayanan dimensi reliability (t= 2,028, p= 0,045), responsiveness (t= 3,135, p= 0,002), assurance (t= 2,613, p = 0,010), dan emphaty (t= 2,480, p= 0,015) berpengaruh positif dan signifikan terhadap kepuasan pasien. Kesimpulan penelitian yaitu kualitas pelayanan berpengaruh signifikan terhadap kepuasan pasien. Kualitas pelayanan dimensi tangible tidak berpengaruh terhadap kepuasan pasien. Kualitas pelayanan dimensi reliability, responsiveness, assurance, dan emphaty berpengaruh positif dan signifikan terhadap kepuasan pasien.